Prediction of return on equity of the energy industry based on equity characteristics - Yang, Yuqi; Wang, Zhenqing (Frontiers in Energy Research, 2023)
This paper mainly uses XGBoost model to predict the Return on equity of enterprises based on equity characteristics. As one of the indicators to measure the operation and performance of enterprises, the Return on equity (ROE) plays a very important role. It is very important for enterprises to improve and integrate in the next business cycle. Therefore, it is of great significance for enterprises to predict the Return on equity of enterprises in the next business cycle scientifically, accurately and timely. This paper takes energy industry enterprises as the research object, analyzes the equity ratio and Return on equity as the starting and ending points, constructs the XGBoost model, and realizes the “prediction” of the future development of enterprises based on the prediction of equity characteristics, which is of positive significance.